Відкриті партійні списки: доцільність впровадження та проблеми їх реалізації - Костишин, Р.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье автор рассматривает актуальные проблемы избирательного законодательства Украины, исследует вопросы открытых партийных списков в современной избирательной системе, а также предлагает ряд предложений и механизмов в отношении устранения упущений и противоречий в действующем законодательстве Украины. The author of the article examines the actual problems of electoral legislation of Ukraine, investigates problems of open party registers in the modern system of election and makes proposals concerning the elimination of gaps and contradictions in the legislation in force. The solution of this problem will secure the function of electoral legislation of Ukraine and will give a new impulse for further development of inner party democracy, personal responsibility for implementation of electoral obligations.